2019
DOI: 10.1101/722462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional properties of habenular neurons are determined by developmental stage and sequential neurogenesis

Abstract: Neural development is not just a linear expansion of the brain. Instead, the structure and function of developing brain circuits undergo drastic alterations that have a direct impact on the animals' expanding behavioural repertoire. Here we investigated the developmental changes in the habenula, a brain region that mediates behavioural flexibility during learning, social interactions and aversive experiences. We showed that developing habenular circuits exhibit multiple alterations, which increase the structur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 114 publications
(217 reference statements)
0
28
0
Order By: Relevance
“…Our multi-day CPA training protocol revealed that 4-week-old zebrafish can recall CPA memories even after 24 h. Adult zebrafish were shown to recall memories encoded by telencephalic neural activity ( Aoki et al., 2013 ), homologous to the mammalian cortex ( Mueller and Wullimann, 2009 ), resembling the memory engrams described in mammals ( Liu et al., 2012 ; Ramirez et al., 2014 ; Kitamura et al., 2017 ). Our results showed a long-term memory recall in juvenile zebrafish with small and relatively translucent brains that are amenable for functional brain imaging ( Jetti et al., 2014 ; Fore et al., 2019 ; Vendrell-Llopis and Yaksi, 2015 ), at single neuron resolution. Future studies will be necessary to further investigate the neural basis of memory at different timescales and to understand how brain regions that are involved in short-term and long-term learning interact with each other to generate memory engrams.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Our multi-day CPA training protocol revealed that 4-week-old zebrafish can recall CPA memories even after 24 h. Adult zebrafish were shown to recall memories encoded by telencephalic neural activity ( Aoki et al., 2013 ), homologous to the mammalian cortex ( Mueller and Wullimann, 2009 ), resembling the memory engrams described in mammals ( Liu et al., 2012 ; Ramirez et al., 2014 ; Kitamura et al., 2017 ). Our results showed a long-term memory recall in juvenile zebrafish with small and relatively translucent brains that are amenable for functional brain imaging ( Jetti et al., 2014 ; Fore et al., 2019 ; Vendrell-Llopis and Yaksi, 2015 ), at single neuron resolution. Future studies will be necessary to further investigate the neural basis of memory at different timescales and to understand how brain regions that are involved in short-term and long-term learning interact with each other to generate memory engrams.…”
Section: Discussionmentioning
confidence: 71%
“…To investigate the ontogeny of CPA learning, we focus on the first 4 weeks of development, during which zebrafish (i.e., nacre mutants with reduced pigmentation) ( Lister et al., 1999 ) are relatively translucent and amenable for functional imaging of dorsal brain regions ( Jetti et al., 2014 ; Fore et al., 2019 ; Vendrell-Llopis and Yaksi, 2015 ). During these first 4 weeks, we observed that the size of zebrafish increased significantly from the larval to juvenile stage ( Figure S1 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In juvenile zebrafish, narp:Gal4 is expressed exclusively in dHb neurons, and it is comparable to adult zebrafish [23] ( Figure S5 A-F). Slightly more lateral location of narp:Gal4 expressing dHb neurons in adults is due to sequential habenular neurogenesis across development [29]. Next, we compared dHb ablated juvenile zebrafish with the control group in a multiday training protocol.…”
Section: Dorsal Habenula Ablation Improves Cpa Learning Performancementioning
confidence: 99%
“…Odors are powerful drivers of a wide range of behavioral responses in fish, such as reproduction, foraging, and defensive behaviors [1][2][3]. The neural pathways underlying these stereotyped behaviors have been the focus of extensive research and are well described [4][5][6][7][8][9][10][11][12][13][14][15]. In the sea lampreys, a neural pathway comprising the olfactory bulb, posterior tuberculum, and mesencephalic locomotor region converts olfactory inputs into locomotor outputs by activating conserved brainstem pre-motor neurons (the reticulospinal neurons) [16][17][18][19], which in turn control the spinal cord locomotor centers [4].…”
Section: Introductionmentioning
confidence: 99%